2000
DOI: 10.1002/j.1551-8833.2000.tb08961.x
|View full text |Cite
|
Sign up to set email alerts
|

DBP formation during chloramination

Abstract: Batch study results may help utilities select appropriate chloramination conditions to limit DBP formation. Batch experiments were conducted on three diverse water sources to study the formation of dissolved organic halogen (DOX), trihalomethanes (THMs), haloacetic acids (HAAs), and cyanogen halides (CNX) during chloramination. The authors used preformed chloramines to examine the effect of pH, mass ratio of chlorine to ammonia–nitrogen (Cl2 to N), and bromide concentration on disinfection by‐product (DBP) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
97
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 13 publications
12
97
0
Order By: Relevance
“…Moreover, DOC influences mobility and, thus, fate of metals (Hiraide, 1992) and organic contaminants (Maxin and Kögel-Knabner, 1995), and negatively affects the use of waters as drinking water through the formation of toxic disinfection by-products (Diehl et al, 2000). For many peatlands, DOC also represents a significant contribution to overall carbon fluxes (Limpens et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DOC influences mobility and, thus, fate of metals (Hiraide, 1992) and organic contaminants (Maxin and Kögel-Knabner, 1995), and negatively affects the use of waters as drinking water through the formation of toxic disinfection by-products (Diehl et al, 2000). For many peatlands, DOC also represents a significant contribution to overall carbon fluxes (Limpens et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an increase in pH also enhances the degradation of these DBPs [20,22]. Diehl et al [21] reported similar results, showing a decrease on different DBP formation with an increase in the pH from 6 to 10, and Yang et al [22] found a marked difference in DBP formation in Suwannee river water, as judged by the range in pH from 4 to 9; the maximum yields of DBPs occurred at pH 5-6. For all these reasons, a pH control would contribute to a significant reduction of DBPs formation [23].…”
Section: Environmental Health Risk V 335mentioning
confidence: 84%
“…With the increasing of Cl 2 /NH 4 -N ratios, chlorine or chloramines previously formed would hydrolyze to form hypochlorous acid (HOCl), which would clearly increase DBP formation. Inversely, Diehl et al [21] reported a decrease in DBP formation during a chloramination experiment when the chlorine-toammonia nitrogen ratio increased. …”
Section: Effect Of Different Parameters On Toxicity Formationmentioning
confidence: 99%
“…Ozonation apparently enhanced the formation of brominated THMs and HAAs. It is generally agreed that DXAA and the brominated HAAs create greater public health concerns (Bull and Angelo, 1995;Diehl et al, 2000). THMs speciation gradually shifts from chlorinated species to mixed bromochloro species with increasing ozone concentration, while only a slight increase of CHBr 3 was detected.…”
Section: Resultsmentioning
confidence: 99%